Perkembangan Sistem Pembayaran di Indonesia : Kebijakan dan Peran Bank Indonesia - Linda Wahyu Ningsih; Rini Puji Astuti; Siti Nur Holisah; Muhamad Syaiful Amin; Muhammad Yunus (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research method uses a qualitative method with a systematic literature review which collects several references from books, journals and previous research to complete this article. The results of this research are that Bank Indonesia plays an important role as a regulator and regulator of the payment system in Indonesia. This involves monitoring transactions so they run safely and avoid fraud. Bank Indonesia also regulates and supervises infrastructure such as ATM networks, debit cards and internet banking. Additionally, they also provide permissions for institutions that wish to participate in the payment system. Bank Indonesia's policies in the Indonesian Payment System Vision and Indonesian Payment System Blueprint 2025 are expected to provide clear direction in utilizing digitalization and maintaining financial system stability. A digital payment system includes money transfer applications, network infrastructure, and regulations governing use of the system. Digital payments also make it possible to purchase goods or services via the internet. Several digital payment applications in Indonesia include Ovo, Dana, Go-Pay, and Qris.